Biodegradation of Environmental Chemicals Pollutants: Evolutionary Insights: Exploring the potential of bioremediation using extracellular enzymes (Journal of Advances and Scholarly Researches in Allied Education, 2017)
An increase in organic pollutant is a major concern in the contemporary world. Organic pollutants may be treated through physical and chemical processes, but these processes are toxic and not environmental friendly because their final product may still remain toxic till the very end. Hence, the biological approaches may be a suitable alternative towards bioremediation practices being not only cost effective but eco-friendly as well. Moreover, the final product happens to be less toxic as compared to other approaches. The microorganisms and plants (bioremediation) are used to remediate the polluted environments widely and is emerging as a promising and appealing area of environmental biotechnology. Apart from using the whole cell microorganisms, the use of their extracellular andor cell-free enzymes has been advocated as an innovative technique to abate pollution. Employment of extracellular enzyme for the removal of pollutants has several advantages over using whole microbial cell. The present review attempts a brief survey of many aspects dealing with the characteristics and potential abilities of both cell-present and cell free extra cellular enzymes in bioremediation of various organic pollutants.